2017
DOI: 10.5194/amt-10-4947-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ozone profiles from DIAL, MLS, and chemical transport model simulations over Río Gallegos, Argentina, during the spring Antarctic vortex breakup, 2009

Abstract: Abstract. This study evaluates the agreement between ozone profiles derived from the ground-based differential absorption lidar (DIAL), satellite-borne Aura Microwave Limb Sounder (MLS), and 3-D chemical transport model (CTM) simulations such as the Model for Interdisciplinary Research on Climate (MIROC-CTM) over the Atmospheric Observatory of Southern Patagonia (Observatorio Atmosférico de la Patagonia Austral, OAPA; 51.6 • S, 69.3 • W) in Río Gallegos, Argentina, from September to November 2009. In this aust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…At Rio Gallegos (51.5°S, 69.3°W) in the southern tip of South America, lidar measurements of the ozone profile were taken in spring 2009 (Wolfram et al, ), and a comparison among the lidar observations, the satellite observations by the Microwave Limb Sounder, and a nudged chemistry‐climate model simulation from September to November was performed (Sugita et al, ). These observations and the model simulation demonstrated changes in the vertical profile of the ozone during the low‐ozone event in November 2009.…”
Section: Time Series Of Observed and Simulated Total Ozone Over Rio Gmentioning
confidence: 99%
“…At Rio Gallegos (51.5°S, 69.3°W) in the southern tip of South America, lidar measurements of the ozone profile were taken in spring 2009 (Wolfram et al, ), and a comparison among the lidar observations, the satellite observations by the Microwave Limb Sounder, and a nudged chemistry‐climate model simulation from September to November was performed (Sugita et al, ). These observations and the model simulation demonstrated changes in the vertical profile of the ozone during the low‐ozone event in November 2009.…”
Section: Time Series Of Observed and Simulated Total Ozone Over Rio Gmentioning
confidence: 99%
“…Laser methods of atmospheric sensing make it possible to determine such physical characteristics of the atmosphere as pressure, temperature and to measure concentrations of gas impurities in a wide range of altitudes (0-100 km) [1][2][3][4]. At present, the main tools of such sensing are laser locators (lidars).…”
Section: Introductionmentioning
confidence: 99%
“…Recent partial column ozone analysis from satellite ozone composites indicates a decadal increase in the upper stratosphere that is statistically significant (WMO, 2014;Harris et al, 2015;Steinbrecht et al, 2017;Ball et al, 2017Ball et al, , 2018Frith et al, 2017), attributed in part to the decline of the ODS. On the other hand, an unexpected decrease in the partial column ozone in the lower stratosphere has been suggested, although with a low level of confidence (Nair et al, 2015;Vigouroux et al, 2015;Ball et al, 2018). A globalscale study (between 60 • N and 60 • S) confirmed a significant decrease in partial column ozone in the lower stratosphere at tropical latitudes with a high level of significance, accounting for a continued and uninterrupted decline of the order of ∼ 2.2 DU between 1998 and 2016 (Ball et al, 2018).…”
Section: Introductionmentioning
confidence: 99%